2005
DOI: 10.1007/s00221-005-0089-8
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous reflexes during rhythmic arm cycling are insensitive to asymmetrical changes in crank length

Abstract: The neural control of a movement depends upon the motor task performed. To further understand the neural regulation of different variations of the same type of movement, we created three dissimilar bilateral rhythmic arm cycling tasks by unilaterally manipulating crank length (CL). Modulation in the amplitude and sign of cutaneous reflexes was used as an index of neural control. Neurologically intact subjects performed three bilateral cycling trials at approximately 1 Hz with the ipsilateral crank arm at one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…Of those 11, 5 had modest adjustments that put them between the long and medium CL and 5 at the short CL. Given the results in the current article, taken together with Hundza and Zehr (2006), we do not think this had a major methodologic impact on our results.…”
Section: Methodologic Considerationscontrasting
confidence: 49%
See 4 more Smart Citations
“…Of those 11, 5 had modest adjustments that put them between the long and medium CL and 5 at the short CL. Given the results in the current article, taken together with Hundza and Zehr (2006), we do not think this had a major methodologic impact on our results.…”
Section: Methodologic Considerationscontrasting
confidence: 49%
“…In those cases (see Table 1), the lengths of the arm cranks were incrementally adjusted (from 19.5 to 3.8 cm) until a comfortable ROM was reached for each subject. A previous study confirmed that this does not significantly alter the motor task, or the reflex modulation of arm cycling (Hundza and Zehr 2006). Additionally, to facilitate holding the cycle handgrips, molded forearm and hand supports were used.…”
Section: Protocolmentioning
confidence: 70%
See 3 more Smart Citations